When Brute Force Fails : How to Have Less Crime and Less Punishment - Kleiman, Mark (Book collections on Project MUSE., 2009)
Since the crime explosion of the 1960s, the prison population in the United States has multiplied fivefold, to one prisoner for every hundred adults--a rate unprecedented in American history and unmatched anywhere in the world. Even as the prisoner head count continues to rise, crime has stopped falling, and poor people and minorities still bear the brunt of both crime and punishment. When Brute Force Fails explains how we got into the current trap and how we can get out of it: to cut both crime and the prison population in half within a decade. Mark Kleiman demonstrates that simply locking up.